A critical assessment of the estrogenic potency of benzyl salicylate. (2021) - Natsch, Andreas; Hostettler, Lu; Haupt, Tina; Laue, Heike
Highlights: Benzyl salicylate (BS) is on priority lists for evaluation of estrogenic effects. New data in both MCF7 (E-screen) and luciferase transactivation assays. Potency of BS is 21′000′000-fold lower than estradiol in transactivation assay. Potency of BS is 36′000′000-fold lower than estradiol in E-screen. Potency is > 1000-fold below human relevant potency threshold. Abstract: Benzyl salicylate (BS) is a natural ingredient of essential oils and a widely used fragrance chemical. A number of in vitro screening studies have evaluated the estrogenic potential of BS with ambiguous results. Lack of dose-response information for the positive control 17β-estradiol (E2) in most studies makes an assessment of the relative potency and efficacy challenging. Notwithstanding this difficulty, BS has been added as the only fragrance ingredient to the list of the first 14 substances to be screened as potential endocrine disruptors by the European Scientific Committee for Consumer Safety (SCCS) and it is included in the Community rolling action plan (CoRAP) of the European REACH regulation to be assessed for the same property. Here we review all literature evidence and present new data to quantify the in vitro potency and efficacy of BS vs. E2 with full dose response analysis in both an estrogen response element (ERE) depending reporter gene assay and in the MCF7 cell proliferation (E-screen) assay. In both assays, very similar results for BS were found. BS is a partial agonist exhibiting 35–47 % maximal efficacy and it is active only close to the cytotoxic concentration. The extrapolated concentration to achieve 50 % efficacy is 21′000′000 higher as compared to E2 in the reporter gene assay. A ca. 36′000′000 higher concentration of BS as compared to E2 is required to reach equivalent partial cell proliferation stimulation in the MCF7 proliferation assay. This potency is significantly below the agonistic activity of known chemicals which cause estrogenic effects in in vivo assays. Importantly, in this study the weak agonistic activity is for the first time directly related to the activity of E2 in a full quantitative comparison in human cell lines which may help ongoing evaluations of BS by regulatory bodies.